Hydroalcoholic extract of Urtica circularis: A neuropharmacological profile - Anzoise, Maria Laura (2013)
Context: The genus Urtica has been known since ancient times. It has known to be useful for the treatment of different human ailments. Objective: The present work evaluated the neuropharmacological effects of a hydroalcoholic extract of Urtica circularis (Hicken) Soraru´ (Urticaceae). Materials and method: The effect on central nervous system of U. circularis hydroalcoholic extract (from leaves and stems) administered by the intraperitoneal route in mice was evaluated by several tests: Pentobarbital- and midazolam-induced hypnosis, open field, hole board, elevated plus-maze and forced swimming. Phytochemical analysis was performed by high-performance liquid chromatography. Results: A total of 300 mg/kg i.p. of the extract produced a significant prolongation of pentobarbital- (40 mg/kg i.p.; 60.1 min versus 25.4 min) and midazolam- (50 mg/kg i.v.; 53.4 min versus 25.1 min) induced sleeping time. The extract?s administration caused a marked reduction of the head-dipping response (DE50: 373 mg/kg i.p.) in the hole-board test. Urtica circularis extract (DE50: 46 mg/kg i.p.) reduced the spontaneous locomotor activity in the open field test. Flumazenil and atropine significantly antagonized the extract?s effect on the locomotor activity. No motor coordination disturbance was observed in the rota rod test at any doses. In the forced swimming test, the extract did not produce any change in the immobility time and it had no significant effects in elevated plus maze test. The phytochemical analysis revealed the presence of chlorogenic acid, vanillic acid, caffeic acid, vicenin-2, p-cumaric acid, ferulic acid, vitexin and isovitexin. Conclusion: This study revealed that U. circularis hydroalcoholic extract possesses sedative activity, facilitating GABAergic and cholinergic transmission.